Tailoring the time delay of optical pulse/sequence employing cascaded SOA and band-pass filter. Issue 11 (16th June 2016) - Wang, Fu; Wang, Zhi; Wu, Chongqing; Mao, Yaya; Shang, Chao; Gao, Kaiqiang; Li, Qiang
Abstract: A tunable time delay for a 100-ps pulse is achieved via a SOA cascaded band-pass filter, which can be tailored by tuning the filter or changing the SOA injection current. For a single pulse, when the pulse propagates through the cascaded system, a delay of 99.6 ps and an advance of 42.6 ps can be achieved by altering the SOA injection current at two different wavelengths located in the red band and blue band of the filter, respectively. The corresponding tunable delay range is 165 ps, and the maximum delay-bandwidth product (DBP) is 1.65. For an optical sequence, to our knowledge, it is the first time that the time delay is tailored over 145.6 ps corresponding to a DBP of 1.46 by tuning the wavelength from 1556.075 to 1556.955 nm, and 45.2 ps (95.6 ps) advance (delay) by tuning the injection current from 100 to 500 mA at 1556.155 nm (1556.955 nm). The dependence of the time delay on the injection current and filtering configuration has been discussed based on plenty of experiments data. Based on SOA's fast switching, this device can be used for signal synchronization and bit-by-bit signal processing in a communication system.